Perbandingan Metode Fuzzy C-Means dan Ward Pada Pengelompokkan Desa Berdasarkan Indikator Potensi Desa - Akolo, Ingka Rizkyani; Pratama, Apriliyanus Rakhmadi; Nadjamuddin, Asriyati (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
Bone Bolango is one of the districts that has experienced many village and sub-district expansion processes. This expansion process changes the village's potential data. Village potential is the carrying capacity for developing villages in order to improve community welfare. In order to accelerate village development, it is necessary to group villages according to their characteristics so that development is more focused and on target. The aim of this research is to group villages based on indicators of village potential so that groups of villages that have the same characteristics can be obtained, as well as to find out the best method for grouping villages in Bone Bolango Regency. The research results show that the optimum cluster for grouping villages in Bone Bolango Regency based on village potential indicators is the cluster using the ward method because it provides the smallest Xie-Beni index value compared to the fuzzy c-means method. The optimum number of clusters is three clusters. Cluster 1 has high average characteristics consisting of 57 villages, cluster 2 has low average characteristics (except livestock production) consisting of 94 villages and cluster 3 has characteristics of large area and high food production consisting of 9 villages.